Pengaruh Pengembangan Karir, Kompetensi SDM serta Sistem Informasi SDM terhadap Kinerja Duta BPJS Kesehatan Cabang Kupang dengan Job Readiness sebagai Variabel Mediasi - Marunduri, Vicktor Jandry; Manafe, Henny A.; Perseveranda, M. E.; Niha, Simon Sia; Man, Stanis (Universitas Batanghari Jambi, 2024)
This research aims to determine the influence of career development, HR competency, and HR information systems on the performance of BPJS Health Ambassadors, Kupang Branch. This research uses a quantitative approach with a survey research design. The population and sample in this study, totaling 36 people, were all BPJS Health Ambassadors, Kupang Branch. Data analysis was carried out using Structural Equation Modeling (SEM) and Partial Least Square (PLS). The results of this research show that there is a significant influence between work readiness, HR information systems, career development, and HR competency on worker output. Work readiness is also significantly influenced by HR competency characteristics and career development, but not significantly by HR information systems. BPJS Health Kupang Branch management is expected to be able to inspire employees and ensure they adapt to changes in the workplace, provide training opportunities or technical assistance to improve skills, recognize each task completion, and update them accurately. personnel records.